Formulation and Antioxidant Activity Test of Rice Bran Extract Cream from Two Varieties of White Rice - Wira Noviana Suhery; Hayu Lestari; Armon Fernando; Fina Aryani; Gressy Novita (Majalah Obat Tradisional, 2023)
Rice bran extract contains high antioxidant compounds. Formulation and antioxidant activity testing of cream preparations containing rice bran extract has been carried out. This study aims to formulate and evaluate cream preparations containing bran extract from two varieties of white rice and their antioxidant activity. The white rice varieties used were the Kalpatali variety (FI) and the Rice 64 (FII) variety. There were three cream formulas, namely the basic formula (F0) and the formula containing rice bran extract with a concentration of 3.1% each (FI and FII). Evaluation of cream preparations included organoleptic test, homogeneity, pH, washability, stability, irritation test, and antioxidant activity test. This study showed that FI has an antioxidant activity of 87.23% and FII has an antioxidant activity of 64.08%. Different varieties of rice show differences in antioxidant activity in cream preparations containing bran extract. The best formula is FI which has good physical properties and higher antioxidant activity compared to FII.Â